Implementation of Differentiated Learning to Improve Student Learning Motivation - Andriyani Dharmawan,; Zuliana, Eka (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to describe the implementation of differentiated learning in improving students' learning motivation in Natural and Social Sciences (IPAS) subjects, especially Physics material about the earth and space in grade VI of SDN 1 Genjahan. This study uses a qualitative descriptive approach with research subjects of teachers and 28 grade VI students. Data collection was carried out through observation, interviews, and documentation, which were then analyzed qualitatively to describe the process and impact of implementing differentiated learning. The results of the study indicate that differentiated learning designed based on variations in student learning styles, namely visual, auditory, and kinesthetic, can increase learning motivation and student engagement in IPAS learning. Adjusting learning strategies to student learning characteristics makes Physics learning more contextual, interesting, and meaningful. Thus, differentiated learning has proven to be effective in improving elementary school students' learning motivation in science subjects and can be used as an alternative learning strategy that is responsive to students' learning needs.